ANALYSIS OF SCHIZOPHRENIA IN SOME EDGAR ALLAN POE'S SHORT STORIES - DJOKO ARDHITYAWAN (AESTHETICS : Jurnal Fakultas Sastra Universitas Gresik, 2018)
Schizophrenia is a split between the intellectual and emotional aspect of the person personality. National Institute of Mental Health (2007) describes the symptoms of schizophrenia into positive, negative and cognitive symptoms. This thesis used descriptive qualitative research; comparison study to analize Edgar Allan PoeÃ¢â‚¬â„¢s short stories, Ã¢â‚¬Å“Tell Tale-HeartÃ¢â‚¬Â, Ã¢â‚¬Å“BereniceÃ¢â‚¬Â. and Ã¢â‚¬Å“The Black CatÃ¢â‚¬Â. The symptoms of schizophrenia are indeed seen in the main character's behavior and utterences which indicates that they are schizophrenic. The main characters experiences positive symptoms such as hallucinations in which they sees and hears vague image around them, delusions which are false beliefs and different than the reality, thought disorder that can be seen from the main character inability to think logically, suffers thought blocking, peserveration and flight of ideas, disorder of movement ( only in Ã¢â‚¬Å“BereniceÃ¢â‚¬Â) , and also negative symptoms, lack of pleasure (only in Ã¢â‚¬Å“The Black CatÃ¢â‚¬Â) . The symptoms directing to the types of schizophrenia. The main character of Ã¢â‚¬Å“Tell Tale HeartÃ¢â‚¬Â suffers paranoid schizophrenia, Ã¢â‚¬Å“BereniceÃ¢â‚¬Â has catatonic schizophrenia, while Ã¢â‚¬Å“The Black CatÃ¢â‚¬Â has undifferentiated schizophrenia. Schizophrenia makes the main character in Ã¢â‚¬Å“Tell Tale HeartÃ¢â‚¬Â gives psychological violences and physical violences to the oldman by killing him, the main character in Ã¢â‚¬Å“BereniceÃ¢â‚¬Â gives physical violence by taking his wifeÃ¢â‚¬â„¢s teeth, and the main character of Ã¢â‚¬Å“The Black CatÃ¢â‚¬Â neglects his family then gives physical violence to his cat and wife by abusing then killing them.